The Interplay between CD27dull and CD27bright B Cells Ensures the Flexibility, Stability, and Resilience of Human B Cell Memory - Ola Grimsholm (Cell Reports, 2020)
Summary: Memory B cells (MBCs) epitomize the adaptation of the immune system to the environment. We identify two MBC subsets in peripheral blood, CD27dull and CD27bright MBCs, whose frequency changes with age. Heavy chain variable region (VH) usage, somatic mutation frequency replacement-to-silent ratio, and CDR3 property changes, reflecting consecutive selection of highly antigen-specific, low cross-reactive antibody variants, all demonstrate that CD27dull and CD27bright MBCs represent sequential MBC developmental stages, and stringent antigen-driven pressure selects CD27dull into the CD27bright MBC pool. Dynamics of human MBCs are exploited in pregnancy, when 50% of maternal MBCs are lost and CD27dull MBCs transit to the more differentiated CD27bright stage. In the postpartum period, the maternal MBC pool is replenished by the expansion of persistent CD27dull clones. Thus, the stability and flexibility of human B cell memory is ensured by CD27dull MBCs that expand and differentiate in response to change. : Grimsholm et al. show that CD27dull and CD27bright represent sequential MBC developmental stages. T cell- and germinal center (GC)-independent CD27dull MBCs are the plastic source of strongly selected and GC-dependent CD27bright MBCs. CD27dull MBCs, able to expand and differentiate in response to change, ensure stability and flexibility of human B cell memory. Keywords: memory B cells, pregnancy, immunological memory, CD27, VH repertoire, immunodeficiency, aging, spleen, vaccine, germinal center